Risk factors influencing seroconversion after inactive SARS-CoV-2 vaccination in people living with obesity - Zehra Kara; Rüveyda Akçin; Ahmet Numan Demir; Harika Oyku Dinc; Bekir Kocazeybek; Volkan Demirhan Yumuk (Obesity Facts, 2022)
Abstract Introduction To investigate the antibody titers against SARS-CoV-2 spike antigens, and the risk factors affecting antibody levels in people living with obesity (PwO) after inactive SARS-CoV-2 vaccine (Corona Vac) administration. Methods 169 consecutive patients with obesity who visited the Center for Obesity Management at Istanbul University-Cerrahpaşa, Cerrahpaşa Medical Faculty Hospitals, between May and August 2021, were invited to the study. The non-obese control group was recruited from 191 subjects who visited the Cerrahpaşa Hospitals Vaccination Unit. The study group and the non-obese control group have already received two doses of inactive SARS-CoV-2 vaccine. SARS-CoV-2 IgG Nucleocapsid Antibody Antibody Test was administered to patients and control subjects to discover those who had prior SARS-CoV-2 infection. Fourty one patients who had prior infection and received two doses of vaccine were also included in the study as a subgroup. Blood samples were taken on the 3rd to 4th week after the second vaccination. SARS-CoV-2 IgG antibody titers were determined by quantitative serological methods. Results Antibody titers against SARS-CoV-2 spike antigen of individuals with BMI 30.0 kg/m2 were significantly lower than those with BMI<30 kg/m2 (p= 0.001) in the study group. Moreover, the antibody titers in people with BMI 30.0 kg/m2 were significantly lower than in those having a BMI<30.0 kg/m2 in the subgroup (p=0.03). Age (p=0.03), BMI (p=0.006) and hypertension (p=0.03) were found to be independent risk factors for antibody response in people living with obesity. Women with non-prior SARS-CoV-2 infection showed a significantly higher antibody response then men (p=0.001). Conclusion SARS-CoV-2 -Immunoglobulin G antibody levels against inactive (CoronaVac) vaccine were found to be lower in people living with obesity (PwO) compared to non-obese individuals. Antibody titers may be measured and booster doses should be delivered accordingly in PwO for optimal protection.